Modeling of the mechanical behavior of composite at different relative humidities - Naceri, A. (Проблемы прочности, 2009)
The moisture diffusion and mechanical response in shear of a laminate constituted of 12 layers of glass fabric fiber/epoxy resin were evaluated. The experimental analysis of the moisture absorption of the specimens conditioned at different relative humidities, 0, 60, and 96% RH at 60°C was to determine the two parameters characteristic of the Fick diffusion law (the diffusion coefficient D and the maximum quantity of water of saturation Mm) which admits the reversibility of the phenomenon. The analysis of the mechanical response in shear of the specimens oriented at 45° tested in uniaxial tension at constant imposed displacement rates, has permitted to show that the influence of the moisture concentration for the composite is very important at 96% RH. The proposed simple model permits to specify the influence of water absorption on the mechanical behavior in shear.